2020
DOI: 10.1109/ojcoms.2020.3035600
|View full text |Cite
|
Sign up to set email alerts
|

Free-Space Optical MISO Communications With an Array of Detectors

Abstract: Multiple-input multiple-output (MIMO) and multiple-input single-output (MISO) schemes have yielded promising results in free space optical (FSO) communications by providing diversity against fading of the received signal intensity. In this paper, we have analyzed the probability of error performance of a muliple-input single-output (MISO) free-space optical channel that employs array(s) of detectors at the receiver. In this regard, we have considered the maximal ratio combiner (MRC) and equal gain combiner (EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 35 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…It can be shown that the probability of error obtained with an array of detectors for an equal gain combining scheme is given by [11]…”
Section: A Equal Gain Combinermentioning
confidence: 99%
See 3 more Smart Citations
“…It can be shown that the probability of error obtained with an array of detectors for an equal gain combining scheme is given by [11]…”
Section: A Equal Gain Combinermentioning
confidence: 99%
“…We observe that the MRC obtains the best error probability performance followed by SC (Max SNR), SC (Max Output) and EGC. This is straightforward since MRC weights the output of each detector optimally [11] as compared to other schemes that weight the detector outputs suboptimally before the fusion takes place. Fig.…”
Section: S R Cmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors in [10] have deliberated upon the signal acquisition performance obtained with an array of detectors receiver for a photon-counting optical channel. The work [11] analyzes the performance of a free-space optical multiple-input single-output receiver for noncoherent and coherent beam combining schemes and pointing errors. For more information on the performance of an array of detectors in a deep-space optical communications, references [12], [13], [14] provide an excellent read.…”
Section: A Background Literature Reviewmentioning
confidence: 99%